Tinjauan Yuridis Promosi Judi Online melalui Live Streaming Youtube: Analisis Pasal 27 Ayat (2) Jo. Pasal 45 Ayat (3) UU ITE dan Pasal 426 KUHP - dwi arifandi; Rasina Padeni Nasution (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The promotion of online gambling through YouTube live streaming has increased significantly alongside the rapid development of digital media and has the potential to encourage the public to access online gambling platforms. This study aims to analyze the legal regulation governing such promotional activities and to examine the legal implications of online gambling promotion through YouTube live streaming under Article 27 paragraph (2) in conjunction with Article 45 paragraph (3) of the Electronic Information and Transactions Law (EIT Law) and Article 426 of Law Number 1 of 2023 concerning the Indonesian Criminal Code. The findings indicate that there is no regulatory gap concerning the promotion of online gambling through YouTube live streaming, as such conduct is specifically regulated under Article 27 paragraph (2) in conjunction with Article 45 paragraph (3) of the EIT Law, while Article 426 of the Indonesian Criminal Code functions as a general provision reinforcing its regulation. Such promotional activities satisfy the elements of a criminal offense because they involve the distribution of electronic information containing gambling-related content while simultaneously offering opportunities to engage in gambling. Therefore, the promotion of online gambling through YouTube live streaming constitutes an unlawful act under the positive law of Indonesia.